2011
DOI: 10.4103/0970-1591.82844
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of the upper urinary tract in patients with bladder cancer

Abstract: Upper urinary tract (UUT) transitional cell carcinoma (TCC) is relatively rare tumor. Approximately 0.7-4% of patients with primary bladder cancer develops UUT-TCC. The symptoms related to an UUT-TCC often occur with an advanced stage which leads one to emphasize a surveillance strategy to monitor the UUT to allow for an earlier diagnosis. Although the risk of UUT-TCC after bladder cancer is well established, there is a paucity of recommendations suggesting the optimal method and frequency of monitoring the UU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The risk factors for UTUC in primary BC are strongly related to the primary tumor risk stratification, where the incidence is as low as 0.7% in the low-risk group, to as high as 24% in high-risk groups ( 16 ). Tumor grade, the presence of carcinoma in situ (CIS), tumor stage, and tumor multiplicity were the factors identified to have an association with the development of UTUC ( 11 , 16 , 17 ). Our result revealed an evidence for the significance of ureteral orifice involvement for further development of UTUC.…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for UTUC in primary BC are strongly related to the primary tumor risk stratification, where the incidence is as low as 0.7% in the low-risk group, to as high as 24% in high-risk groups ( 16 ). Tumor grade, the presence of carcinoma in situ (CIS), tumor stage, and tumor multiplicity were the factors identified to have an association with the development of UTUC ( 11 , 16 , 17 ). Our result revealed an evidence for the significance of ureteral orifice involvement for further development of UTUC.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with primary bladder cancer, the risk of UTUR is <4% 5, 6. It has been reported that the overall prevalence of transitional cell carcinoma within the upper tract urothelium following cystectomy ranged from 0.75% to 6.4% 3.…”
Section: Introductionmentioning
confidence: 99%